Mapping the Queer Body: Queer Tropes and Malayalam Cinema - Rajesh James; Sathyaraj Venkatesan (Wacana Seni Journal of Arts Discourse, 2022)
The narrative logic of mainstream Malayalam cinema is often predicated on heteronormative values and homophobic social practices. Though representations of LGBTQIA+ (lesbian, gay, bisexual, transgender, queer, intersex, asexual and agender) desires (both individual and collective) have been subject to changes particularly after the historical verdict of 2018, mainstream Malayalam cinema is quite reluctant to explore “the love that had for so long been left out in the cold” (Griffiths 2008, 130). Barring a few exceptions, most of the films produced in Kerala (since Malayalam cinema’s inception in 1928) have characterised LGBTQIA+ as aberrant, abnormal, or deviant. Having said that, there have been considerable efforts from progressive filmmakers to critique and subvert the homophobic sentiments of the society and engage with queer desires in Malayalam cinema either denotatively or connotatively. This has been made possible due to their exposure to variegated cultural values as a result of the changing socio-economic and political conditions. By identifying three major tropes (the closeted queer body, the stereotyped queer body, and the visible queer body) in queer filmic representations, the paper attempts to map the many expressions of queer subjectivities in Malayalam cinema. In the process, the article demonstrates how queer cinema in Malayalam disrupts heteronormativity using its queer aesthetics.